Analisis Perbandingan Algoritma Advanced Encryption Standard Untuk Enkripsi Short Message Service (SMS) Pada Android - Fredianto Fredianto; Ari Kusyanti; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Short Message Service (SMS) is a popular service among mobile phone users in Indonesia. The biggest security gap in SMS communications is that it can read messages and save them to the Short Message Service Center (SMSC) when an SMSC attack occurs. One solution to solve the problem is by encoding messages that are sent or better known as encryption. In this research, AES 128 AES, AES 192 bits AES and AES 256 bits are used for SMS message encryption on Android. The Elliptic Curve Diffie-Hellman (ECDH) protocol is used in key exchange mechanisms for encryption and decryption of messages. In this study obtained the longer the data will be the longer the process of encryption and decryption. In this research, there is no significant performance difference, it is proved by ANOVA test which has been done with each data length.